If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 = 2v + 6 Reorder the terms: -2 = 6 + 2v Solving -2 = 6 + 2v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-2v' to each side of the equation. -2 + -2v = 6 + 2v + -2v Combine like terms: 2v + -2v = 0 -2 + -2v = 6 + 0 -2 + -2v = 6 Add '2' to each side of the equation. -2 + 2 + -2v = 6 + 2 Combine like terms: -2 + 2 = 0 0 + -2v = 6 + 2 -2v = 6 + 2 Combine like terms: 6 + 2 = 8 -2v = 8 Divide each side by '-2'. v = -4 Simplifying v = -4
| -31=-7+4u | | 1.20*400= | | -8+3y=-23 | | 2(x+12)=0 | | (2x-17)=(3x+10) | | -24=4(1+x) | | 26=3w-10 | | 2s-6=4 | | 9w/3 | | 2w+13=29 | | X^2+2x+y^2-10=0 | | 49=4v+9 | | -1=x/15 | | 3u-8=40 | | 5d+3=18 | | 5x+3=-x-21 | | 5n-1+5n-3=26 | | h=372/(3x*x) | | 2x+5+c=0 | | x-x^2-2x=0 | | 14x-5+5-12x= | | 100x+500y=400 | | b(b+2)=4 | | 2-3=10 | | (m*(m-1))/2 | | 4m^2+30m+16=0 | | -7x-2=-6x+3 | | m*(m-1)*(m-2)/6 | | 7x-56=-6x+21 | | 8x^2+6x+1+0=0 | | t/7=6/42 | | 8-2x+3=2x+5 |